Comparing the performance of market-based and accounting-based bankruptcy prediction models - Agarwal, Vineet; Taffler, Richard J. (Elsevier Science B.V., Amsterdam., 2008)
Recently developed corporate bankruptcy prediction models adopt a contingent claims valuation approach. However, despite their theoretical appeal, tests of their performance compared with traditional simple accounting-ratio-based approaches are limited in the literature. We find the two approaches capture different aspects of bankruptcy risk, and while there is little difference in their predictive ability in the UK, the z-score approach leads to significantly greater bank profitability in conditions of differential decision error costs and competitive pricing regime. (C) 2007 Published by Elsevier B.V.